The Formation and Evolution of Islamic Studies Educational Program in Kazakhstan through the Integration of Local Culture and Secular Principles - Mustafayeva, Anar; Kaliyeva, Shynar; Mukhitdinov, Rashid; Paltore, Yktiyar (Ulumuna, 2025)
Kazakhstan, after the collapse of the Soviet Union and the acquisition of independence, chose a secular path in religion after seventy years of atheism. The state adopted a secular direction, but society, consisting of a Muslim-majority population, began a natural process of cultural revival – language, history, religion, and traditions – restoring religious values. Islamic education became a way of religious revival, based not only on Islam but also on local culture and Kazakhstan’s policy on religion. Higher Islamic education in Kazakhstan became part of bachelor’s, Master’s, and doctoral programs (PhD) in Islamic studies. This article examines the formation and development of higher Islamic education in Kazakhstan through the example of the only Islamic university. Quantitative and qualitative indicators from the analysis of the educational program, showing a balance between Islamic, secular, and Kazakh culture-related disciplines, emphasize the possibility of development in this direction, adhering to Islam, secularism, and culture.